Bioprinting and plastic compression of large pigmented and vascularized human dermo-epidermal skin substitutes by means of a new robotic platform. (August 2022) - Pontiggia, Luca; Van Hengel, Ingmar AJ; Klar, Agnes; Rütsche, Dominic; Nanni, Monica; Scheidegger, Andreas; Figi, Sandro; Reichmann, Ernst; Moehrlen, Ueli; Biedermann, Thomas
Extensive availability of engineered autologous dermo-epidermal skin substitutes (DESS) with functional and structural properties of normal human skin represents a goal for the treatment of large skin defects such as severe burns. Recently, a clinical phase I trial with this type of DESS was successfully completed, which included patients own keratinocytes and fibroblasts. Yet, two important features of natural skin were missing: pigmentation and vascularization. The first has important physiological and psychological implications for the patient, the second impacts survival and quality of the graft. Additionally, accurate reproduction of large amounts of patient's skin in an automated way is essential for upscaling DESS production. Therefore, in the present study, we implemented a new robotic unit (called SkinFactory) for 3D bioprinting of pigmented and pre-vascularized DESS using normal human skin derived fibroblasts, blood- and lymphatic endothelial cells, keratinocytes, and melanocytes. We show the feasibility of our approach by demonstrating the viability of all the cells after printing in vitro, the integrity of the reconstituted capillary network in vivo after transplantation to immunodeficient rats and the anastomosis to the vascular plexus of the host. Our work has to be considered as a proof of concept in view of the implementation of an extended platform, which fully automatize the process of skin substitution: this would be a considerable improvement of the treatment of burn victims and patients with severe skin lesions based on patients own skin derived cells.